DFPI-based Control of the DC-bus Voltage and the AC-side Current of a Shunt Active Power Filter - Nabil Elhaj; M. Brahim Sedra; Hind Djeghloud (Bulletin of Electrical Engineering and Informatics, 2016)
The current paper presents a continuation of an earlier research and purposes to enhance the performances of the studied system. While the double fuzzy PI (DFPI) control was applied only on the DC capacitor bus in a previous work it is applied here also on the output current of shunt active power filter (SAPF). The nonlinear load disrupts the electrical distribution system by the generation of harmonics, which requires an efficient SAPF intervention to minimize the effects of harmonics on the network and provide electrical energy conforms to international standards. The design and simulation of this work were performed under MATLAB/Simulink environment. The carried-out simulation results demonstrate a satisfactory regulation both for the output current of the SAPF and the DC bus voltage. Furthermore the power quality is improved since a near-unity power factor and very low rates of imbalance of both source voltages and currents are obtained.